How Confident Are High Schoolers to Speak English: A Report on Speaking Self-Efficacy Survey - Muhammad Iklil Zaki; Alies Poetri Lintangsari (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
Speaking in English is one of the toughest aspects to master in acquiring the English language. This is reflected in the broad job vacancies that require English as a mandatory skill. It means that it is important to equip students with adequate English skills. However, several reports have found that many students still lack confidence in speaking. On the other hand, a well-known theory suggests that one of the prominent factors influencing learning achievement is confidence, specifically called efficacy. Students' self-efficacy level seems to be one of the prominent factors that could influence their speaking achievement. As the pandemic has transformed the learning mode back into traditional face-to-face learning, this current study was conducted to investigate students' self-efficacy level in public speaking in the post-pandemic era. The study utilized a quantitative method and employed a questionnaire adapted from Paradewari's article. The questionnaire was converted into two types, online and offline conditions, and distributed to 182 students. An independent t-test method was used to compare whether there were differences in students' self-efficacy levels in public speaking between online and offline learning. The study revealed a significant difference in the overall students' self-efficacy level (as indicated by the T-Test Result score) and the factors influencing it. It also found that offline learning had a more positive effect on students' self-efficacy in public speaking compared to online learning.